Why ARMAX-GARCH linear models successfully describe complex nonlinear phenomena: A possible explanation - Hung T. Nguyen (2018)
© Springer International Publishing Switzerland 2015. Economic and financial processes are complex and highly nonlinear. However, somewhat surprisingly, linear models like ARMAX-GARCH often describe these processes reasonably well. In this paper, we provide a possible explanation for the empirical success of these models.